Recomendação de curvas e valores de referência para avaliar o crescimento de crianças nascidas pré-termo - Pereira-Da-silva, Luis (2021)
The growth charts and reference values for preterm infants are revisited and recommendations for their use are updated by the Portuguese Neonatal Society. To assess intrauterine growth: The cross-sectional sex specific Fenton 2013 charts, based on birth weight, length, and head circumference, are the most appropriate. Neonates born with weight < 3rd percentile are classified as small-for-gestational-age and those born > 97th percentile are classified as large-for-gestational-age. The Olsen 2015 body mass index curves can be used to assess proportionality at birth, although the accuracy of some length measurements has been questioned. During hospitalization: The online calculator at www. growthcalculator.org, based on recent longitudinal curves, is recommended to assess weight gain; it provides an accurate graphic display of the current weight percentile, target weight, and its deviation. Fenton 2013 charts may be an alternative to monitor linear and head growth while in the neonatal unit. In the neonatal period, growth rates of 15-20 g/kg/day for weight, 0.9-1.1 cm/week for length, and 0.9-1.0 cm/ week for head circumference, are adequate goals. After discharge: The longitudinal Intergrowth-21st standards are adequate to monitor growth from 32-64 weeks’ postmenstrual age, for infants born at more than 27 weeks of gestation. After that postmenstrual age, the World Health Organization growth standards 2006 for infants born at term can be used.